The Funniest thing you never said : The Ultimate collection of humorous quotations
It\'s back! The bestselling, blockbusting, bumper book of humorousquotations rides back into town with over 6,000 new quotes. Fromtimes past to the modern day, classic funnies to contemporary wit,\The Funniest Thing You Never Said 2\ delivers an unbeatableselection of fantastic and hilarious quotes on every subject underthe sun. Featuring topics as diverse as celebrity to religion, andincluding a cast of quotees ranging from Oscar Wilde to HomerSimpson, there\'s something here for everyone with a sense of humour.\'I am willing to love all mankind, except an American\' - SamuelJohnson. \'Glastonbury was very wet and muddy. There was trench foot,dysentery, peaches ...all the Geldof daughters\' - Sean Lock.\'Politics would be a helluva good business if it weren\'t for thegoddamned people\' - Richard Nixon. \'I\'ve had more women than mostpeople have noses\' - Steve Martin. \'I have the simplest tastes. I\'malways satisfied with the best\' - Oscar Wilde. \'Well, it\'s 1 a.m.Better go home and spend some quality time with the kids\' - HomerSimpson. \'All I know is I\'m not a Marxist\' - Karl Marx. \'I\'m the pinksheep of the family\' - Alexander McQueen.